2019
DOI: 10.1002/acr.23816
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated With Bone Erosion in Patients With Gout

Abstract: Objective. To determine the prevalence, distribution, and factors associated with bone erosion detectable by ultrasound in patients with gout.Methods. Ultrasound scans were performed in 980 patients with gout, and bone erosion was detected. The prevalence and distribution of bone erosion in gout patients were calculated. Both clinical variables and ultrasound signs were entered into a multivariate logistic regression analysis to clarify the factors associated with bone erosion in patients with gout.Results. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 24 publications
3
14
2
Order By: Relevance
“…ULT may diminish HAG and improve synovitis and synovial hypertrophy. Bone erosion was known to be an irreversible injuriousness in gout [23]. In our study, tophi and DCS were both found to be correlated with bone erosion.…”
Section: Discussionsupporting
confidence: 60%
“…ULT may diminish HAG and improve synovitis and synovial hypertrophy. Bone erosion was known to be an irreversible injuriousness in gout [23]. In our study, tophi and DCS were both found to be correlated with bone erosion.…”
Section: Discussionsupporting
confidence: 60%
“…ULT may diminish HAG and ameliorate synovitis or synovial hypertrophy. Bone erosion was known to be an irreversible injuriousness in gout (23). In our study, Tophi and DCS were both found to be correlated with bone erosion.…”
Section: Discussionsupporting
confidence: 60%
“…The biological processes involved in MSU crystal formation are not yet clear; further analysis is needed regarding whether humoral immune changes caused by poor sleep habits stimulate the formation and deposition of MSU crystals. In addition, preferential deposition in tissues with minimal vascularisation (e.g., tendons, ligaments, and cartilage) implies that sleep quality has a profound effect on vascular function (24). Sleep deprivation can impair the function of vascular endothelial cells by inducing sympathetic nervous system activation, systemic in ammation, or oxidative stress; these changes reduce blood supply to tissues, which may increase MSU deposition (25).…”
Section: Discussionmentioning
confidence: 99%